Obesity risk factors in American Indians and Alaska Natives: a systematic review. (September 2019) - Zamora-Kapoor, A.; Sinclair, K.; Nelson, L.; Lee, H.; Buchwald, D.
Abstract: Objectives: We systematically reviewed the literature on risk factors for obesity in American Indians (AIs) and Alaska Natives (ANs) of all ages. Study design: We searched titles and abstracts in PubMed with combinations of the following terms: obesity, body mass index (BMI), American Indian, Alaska Native, and Native American. Methods: We limited our review to articles that provided an empirically testable claim about a variable associated with obesity, measured obesity as a dependent variable, and provided data specific to AI/ANs. Results: Our final sample included 31 articles; 20 examined AI/AN youth (<18 years), and 11 examined AI/AN adults (≥18 years). Risk factors for obesity varied by age. In infants, low birth weight, early termination of breastfeeding, and high maternal BMI, and maternal diabetes increased the risk of childhood obesity. In children and adolescents, parental obesity, sedentary behaviors, and limited access to fruits and vegetables were associated with obesity. In adulthood, sedentary behaviors, diets high in fats and carbohydrates, stress, verbal abuse in childhood, and the belief that health cannot be controlled were associated with obesity. Conclusions: Extant studies have three limitations: they do not apply a life course perspective, they lack nationally representative data and have limited knowledge of the resilience, resistance and resourcefulness of AI/ANs. Future studies that avoid these shortcomings are needed to inform interventions to reduce the prevalence of obesity in AI/ANs across the life course. Highlights: American Indians and Alaska Natives have the highest prevalence of obesity in the United States. No study to date has examined the most important risk factors for obesity in this population. Obesity reduces life expectancy, increases mortality and morbidity, and exacerbates health disparities. The most important risk factors for obesity in American Indians and Alaska Natives vary by age. Research lacks nationally representative data and knowledge of the role of resilience in obesity prevention efforts.